The control of aspergillosis in bird collections - Beer, J V (Wildfowl, 1959)
At present, cure of the disease is not possible as there is no reliable diagnostic method, and drugs, such as Nystatin, have yet to be proven effective. The best approach is therefore one of prevention, and the easiest way is to provide and maintain a good standard of hygiene in the collection area. Basically any large concentration of the fungus Aspergillus fumigatus must be removed and destroyed, and further build up prevented.